2020
DOI: 10.1530/rep-20-0215
|View full text |Cite
|
Sign up to set email alerts
|

Pluripotent stem cells are insensitive to the cytotoxicity of TNFα and IFNγ

Abstract: Recent studies have demonstrated that embryonic stem cells (ESCs) have an underdeveloped innate immune system, but the biological implications of this finding are poorly understood. In this study, we compared the responses of mouse ESCs (mESCs) and mESC differentiated fibroblasts (mESC-FBs) to tumor necrosis factor α (TNFα) and interferons (IFNs). Our data revealed that TNFα, IFNα, IFNβ, or IFNγ alone do not cause apparent effects on mESCs and mESC-FBs, but the combination of TNFα and IFNγ (TNFα/IFNγ) showed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 30 publications
2
16
0
Order By: Relevance
“…TNF-a and IFN-g are known as "embryotoxic cytokines" for their detrimental effect on early embryos when dysregulated (35). Remarkably, mESCs, hESCs, and hiPSCs were insensitive to the cytotoxicity of TNF-a/IFN-g or any of the above-mentioned cytokines alone (9,22,23). Therefore, we proposed that the attenuated innate immune response in ESCs could be an adaptive feature for ESCs to avoid immunological insults in a blastocyst (1).…”
Section: Attenuated Innate Immune Response-a Common Feature Of Escs A...mentioning
confidence: 99%
See 2 more Smart Citations
“…TNF-a and IFN-g are known as "embryotoxic cytokines" for their detrimental effect on early embryos when dysregulated (35). Remarkably, mESCs, hESCs, and hiPSCs were insensitive to the cytotoxicity of TNF-a/IFN-g or any of the above-mentioned cytokines alone (9,22,23). Therefore, we proposed that the attenuated innate immune response in ESCs could be an adaptive feature for ESCs to avoid immunological insults in a blastocyst (1).…”
Section: Attenuated Innate Immune Response-a Common Feature Of Escs A...mentioning
confidence: 99%
“…The molecular basis underlying the attenuated innate immune response in ESCs is not completely understood. Studies have shown that the major receptors for viral RNA (TLR3, RIG-I, and MDA5), LPS (TLR4), and TNF-a (TNFR1) are either expressed at low levels or not functional in ESCs (6,9,10,23). More importantly, NF-kB, the master transcription factor in mediating many types of immune responses, is inactive in ESCs (8,9,3941).…”
Section: Attenuated Innate Immune Response-a Common Feature Of Escs A...mentioning
confidence: 99%
See 1 more Smart Citation
“…The subsets of expressed ISGs are distinct between different stem cell types and change in differentiation (Wu et al , 2018). How these ISGs are regulated is unknown, as mouse ESCs for example do not respond to interferon (IFN) stimulation (Burke et al , 1978; Harada et al , 1990; Wang et al , 2013; Chen et al , 2020). Strikingly, pluripotent stem cells are more resistant against viral infection compared with their differentiated descendants (Swartzendruber & Lehman, 1975; Wolf & Goff, 2009), and this is at least in part due to ISG expression (Wu et al , 2018).…”
Section: Introductionmentioning
confidence: 99%
“…While it is not clear which factors are involved in the formative pluripotency network, stem cells intrinsically express a subset of genes which are referred to as interferon stimulated genes (ISGs) (Wu et al 2018). How these ISGs are regulated is unclear, as stem cells do not respond to interferon stimulation (Burke, Graham, and Lehman 1978; Harada et al 1990; Chen et al 2020). At the same time, stem cells are resistant against viral infection (Swartzendruber and Lehman 1975; Wolf and Goff 2009).…”
Section: Introductionmentioning
confidence: 99%